Think Pair Share Type Cooperative Learning Model: Dampaknya terhadap Kemampuan Menulis Karangan Eksposisi - Muhammad Singgih (STKIP PGRI Bandar Lampung, 2023)
In improving students' exposition essay writing skills, the right learning model is needed, so as to make learning creative and innovative. This study aims to analyze the learning outcomes of writing exposition essays using the think pair share learning model. The method used is quantitative with the type of experiment. Data was collected through tests, interviews and documentation on grade VIII students of SMPN 35 Bandar Lampung. The results of this study found that the results of the normality test were experimental 0.156 > 0.05 and control 0.104 > 0.05 which means normal, the linearity ui is 0.883 > 0.05 which means linear and the results of a simple linear regression test are 0.000 < 0.05 which means it has an influence. So it can be concluded that the think pair share learning model has an influence on writing exposition essays. Keywords: Cooperative Learning, Think Pair Share, Writing